PS-C30-11: EFFECTS OF SGLT-2 INHIBITORS ON 24 H AMBP IN PATIENTS WITH TYPE 2 DIABETIC AND HYPERTENSION: A SYSTEMATIC REVIEW AND META-ANALYSIS. (January 2023) - Wang, Qiongying; Tian, Li; Yu, Jing; Bai, Feng
Abstract : Objective: To analyze the effects of different types of sodium-glucose cotransporter 2 inhibitors (SGLT2i) on 24-hour ambulatory blood pressure in patients with type 2 diabetes mellitus and hypertension. Method: In the meta-analysis, The PubMed, Web of science, and Cochrane Library were searched for relevant literature, and the references obtained from these sources were retrieved from inception till December 2020, Using sodium-glucose cotransporter 2 inhibito, hypertension and randomized controlled trial as keywords. The inclusion and exclusion criteria were formulated in accordance with the requirements of Cochrane systematic review. A total of 1354 articles were retrieved, 592 duplicate articles were excluded, 372 articles were excluded after reading the title and abstract, 87 articles were excluded from non-randomized control and irrelevant outcome indicators, and 7 studies with 2343 patients were finally included. Use RevMan5.3 software to compare the changes in 24-hour ambulatory blood pressure, day and night blood pressure of patients with type 2 diabetes and hypertension before and after treatment with different types and doses of SGLT2i. Results: A total of four types of SGLT-2i (Empagliflozin, Canagliflozin, Dapagliflozin, Ertugliflozin) were evaluated in the application of patients with type 2 diabetes and hypertension. The result showed that compared with placebo, SGLT2i could reduce the 24-hour systolic blood pressure of patients with type 2 diabetes and hypertension by 4.36mmHg, among which the antihypertensive effects of empagliflozin, canagliflozin, dapagliflozin and ertugliflozin were -4.59mmHg, -3.74mmHg, -5.06mmHg, -3.64mmHg, respectively; similarly, the 24-hour dynamic diastolic blood pressure decreased by 2.20mmHg, among which the antihypertensive effects of empagliflozin, canagliflozin, dapagliflozin and ertugliflozin were -2.38mmHg, -1.22mmHg, -2.00mmHg, - 2.69mmHg, respectively. At the same time, the systolic and diastolic blood pressure during the day and night decreased significantly. Conclusions: This meta-analysis shows that SGLT2i can have beneficial effects on the cardiovascular system by reducing 24-hour ambulatory blood pressure in patients with type 2 diabetes and hypertension, other than reducing blood sugar. Therefore, for patients with type 2 diabetes and hypertension, SGLT2i may be the best hypoglycemic choice.